2014
DOI: 10.1002/lary.24885
|View full text |Cite
|
Sign up to set email alerts
|

In‐office balloon catheter dilation: Analysis of 628 patients from an administrative claims database

Abstract: Objectives/Hypothesis: Balloon catheter dilation (BCD) of the paranasal sinuses is increasingly described as a standalone procedure in the office for minimally invasive treatment of patients with chronic rhinosinusitis (CRS). This study evaluates CRS-related healthcare utilization before and after in-office treatment as performed by otolaryngologists within the United States in an all-comer population.Study Design: Retrospective claims database analysis. Methods: The MarketScan database was queried for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…The observed complication rate after BCD was almost double compared to previously reported values. In 2015, Sillers et al identified seven cases of hemorrhage and two orbital complications in 628 in‐office BCD cases . The higher rate described here is possibly secondary to the combination of the BCD procedure with other sinonasal procedures (i.e., septoplasty and FESS), which carry a higher risk of complications on their own.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The observed complication rate after BCD was almost double compared to previously reported values. In 2015, Sillers et al identified seven cases of hemorrhage and two orbital complications in 628 in‐office BCD cases . The higher rate described here is possibly secondary to the combination of the BCD procedure with other sinonasal procedures (i.e., septoplasty and FESS), which carry a higher risk of complications on their own.…”
Section: Discussionmentioning
confidence: 75%
“…In 2015, Sillers et al identified seven cases of hemorrhage and two orbital complications in 628 in-office BCD cases. 21 The higher rate described here is possibly secondary to the combination of the BCD procedure with other sinonasal procedures (i.e., septoplasty and FESS), which carry a higher risk of complications on their own. Of interest, the cases of serious complications (orbital chemosis/proptosis and facial subcutaneous emphysema) were both in patients who underwent BCD in isolation and who had Lund-Mackay scores of 0.…”
Section: Discussionmentioning
confidence: 88%
“…Further controlled prospective studies with increased patient numbers are, thus, needed to show which patients benefit the most from the balloon sinuplasty, so that the obvious benefits of this tool can be efficiently utilized. Moreover, it could be possible to speculate that balloon sinuplasty might establish a position as an in-office treatment option for CRS patients with plain obstructive disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…Health care resource utilization and costs HCRU and costs related to CRSwNP were reported in five studies ( Supplementary Table 15) [97][98][99][100][101] . Four studies were conducted in the United States 97,99-101 and one study in China 98 .…”
Section: Direct Costsmentioning
confidence: 99%